Vermicomposting for municipal solid waste recycling to promote green technology - Idris, Azni; Abd Aziz, Nor Azwady; Wan Ab. Karim Ghani, Wan Azlina; Bawon, Paiman; Abd. Ghani, Awang Noor; Mohd Don, Azura; Sharif, Mohd Hafiz; Zam @ Zambahari, Rozaini (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Vermicomposting is a green method of reducing municipal solid waste and the byproduct can be utilised as biofertilizer. This KTP project was aimed at transferring valuable knowledge on how to convert organic wastes using special worms. This project had created public awareness in the urban waste reduction and promote the use of vermicompost recycling practices. Transfer of technology involved setting up training and construction of a pilot scale vermi-compost centre at Pasar Sri Serdang where MPSJ was able to show to the public that everyone can participate in waste management. The pilot project at Pasar Serdang employed latest method where all waste vegetables in the market can be turned into bio-compost in a single step without hazards of bad smell and it requires a shorter time (30%) compared to conventional composting process. Throughout the program, the knowledge was transferred to MPSJ, community partners, students and the market traders at Taman Sri Serdang, Selangor. Method of making vermicompost bin, collect of vermicompost, monitoring of process was given by the experts. Organized training courses for operators MPSJ was completed on site. About 60 % waste reduction can be achieved using vermicomposting, and in return a valuable compost product can be sold for the city landscape.